Association between patient factors and hospital completeness of a patient-reported outcome measures program in joint arthroplasty, a cohort study - Ian A. Harris; Yi Peng; Kara Cashman; Ilana Ackerman; Emma Heath; Neville Rowden; Stephen E. Graves (SpringerOpen, 2022)
Plain English summary Hospitals vary in how completely they include and follow up patients when measuring patient-reported health. It is important to know if the completeness of inclusion and follow up by hospitals is affected by patient characteristics. This study addresses that problem by using data from a national patient outcome survey involving over 30,000 patients from 43 hospitals to look at the correlation between certain patient characteristics (like age, sex, obesity and general health) and the rates of inclusion and follow up for each hospital. Rates of inclusion (registering patients in the program) and follow up rates varied widely between hospitals (from 5 to 87%). The rates of inclusion and follow up were not correlated with patient age, sex, body mass index or their general health. These findings suggest that the variation between hospitals in the rates of inclusion of joint replacement patients in health surveys are not due to differences in patient characteristics. The differences may be due to local hospital factors, such as resources and clinician engagement.